Synergistic effects of the mixing factor on the kinetics and products obtained by co-pyrolysis of Rosa rubiginosa rosehip seed and husk wastes - Torres Sciancalepore, Rodrigo Agustin (2024)
The aim of this work was to study the potential synergistic effects of the mixing factor on the kinetics parameters and products obtained through co-pyrolysis of two wastes from Rosa rubiginosa rosehip, and further co- gasification with CO2 of the remaining biochar. Thermogravimetric analysis showed that 6 different processes occur by slow pyrolysis (heating rates of 5, 10, and 20 ◦C/min), associated with the decomposition of hemi- celluloses, cellulose, lignin, and CaCO3 from the ashes. Isoconversional methods determined activation energies of 84.68?223.42, 230.11?270.85, 187.58?303.37, and 400.11?421.71 kJ/mol for hemicellulose, cellulose, lignin, and CaCO3 decomposition, respectively. In most cases, the activation energy from co-pyrolysis was higher for the blends than for the pure wastes, which means that the blends are less reactive to pyrolysis. Gas and tar analyses showed that the blend with 75 % husk waste and 25 % seed waste produced the most hydrogen (5.639 mmol/g biomass), while the blend with 25 % husk waste and 75 % seed waste produced the most carbon monoxide (3.642 mmol/g biomass). The biochar produced by the blends and pure wastes were thermally treated with CO2 to compare reactivity to gasification. It was concluded that the addition of husk waste to the blend increases the reactivity of the biochar obtained, mainly due to its higher ash content.